2006
DOI: 10.1007/s00167-006-0144-4
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic collagen meniscus implant results at 6 to 8 years follow up

Abstract: Meniscal substitution is a fundamental procedure to prevent osteoarthritis of the knee after massive meniscectomy. Stone, Steadman and Rodkey have developed a bioreadsorbable collagen matrix (CMI) which acts as a scaffold to restore the original medial meniscal. The objective of this study was to prospectively evaluate the results of CMI implantation at a follow up from a minimum of 6 to a maximum of 8 years. Eight patients (mean age 25) were evaluated at a final observation point from 6 to 8 years after CMI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(106 citation statements)
references
References 46 publications
5
97
1
3
Order By: Relevance
“…In a dog model, the resorbable bovine collagen scaffold developed by Stone et al 40 for regeneration of meniscal tissue showed host tissue ingrowth and formation of fibrocartilage resembling a normal canine meniscus after 9 and 12 months. 12 A clinical trial concerning CMI revealed encouraging results, 10,11,13,14 but long-term, histological and MRI results are controversial and evidence of chondroprotection is still pending. In contrast to the present study, the CMI is used for partial meniscal substitution because a residual rim of the original meniscus is necessary to fix the CMI, which makes the comparison of our results difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a dog model, the resorbable bovine collagen scaffold developed by Stone et al 40 for regeneration of meniscal tissue showed host tissue ingrowth and formation of fibrocartilage resembling a normal canine meniscus after 9 and 12 months. 12 A clinical trial concerning CMI revealed encouraging results, 10,11,13,14 but long-term, histological and MRI results are controversial and evidence of chondroprotection is still pending. In contrast to the present study, the CMI is used for partial meniscal substitution because a residual rim of the original meniscus is necessary to fix the CMI, which makes the comparison of our results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, their long-term success, durability, safety, and chondroprotective effects are still uncertain. 8,9 The CMI (ReGen Biologics, Franklin Lakes, NJ) is the only scaffold used so far in a clinical setting, [10][11][12][13][14] even if CMI cannot be considered as total meniscal substitute as a residual rim of the original meniscus is necessary to fix the implant. Despite improvements in pain and selfevaluation, 12 the histological and magnetic resonance imaging (MRI) results remain controversial.…”
Section: Introduction Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagen meniscus implant (CMI) (ReGen Biologics, Franklin Lakes, NJ) is the first regenerative technique applied to meniscal tissue in clinical practice (Stone et al, 1992;Stone et al, 1997;Steadman and Rodkey, 2005;Zaffagnini et al, 2007). Since an outer rim of meniscal tissue is needed for CMI implantation, it is indicated only for partial and not total meniscus regeneration.…”
Section: Cell-free Techniquesmentioning
confidence: 99%
“…However, these studies demonstrated the safety of the technique [23]. Zaffagnini et al [25] published a study with 8 patients with a follow-up of 6-8 years and good clinical and radiological results. However, a second-look arthroscopic assessment and magnetic resonance imaging (MRI) revealed the deterioration of the implant over time, with a considerable reduction in size or the complete degradation of the implant.…”
Section: Collagen Matrix Scaffoldsmentioning
confidence: 99%